Effects Of Cognitive Conflict Instructional Strategy And Motivation On Conceptual Change And Attitude Towards Algebra Among Tenth Graders In The UAE - Alrababah, Yasseen Mohammad Ahmad (2022)
The purpose of this study was to determine the effects of cognitive conflict instructional strategy and motivation on conceptual change in algebra and attitude towards algebra among Tenth Graders in United Arab Emirates. This study employs a quasi-experimental research design, namely non-equivalent control group research design. To collect data, both quantitative and qualitative methods were used. The researcher used Face to Face Interview Protocol (FFIP) and Pre-Conceptual Change in Algebra Test (PreCCAT) to identify and classify common algebra misconceptions. The researcher adapted a Motivation to Engage in Conceptual Change Questionnaire (MECCQ) to measure level of student’s motivation to engage in conceptual change. Pre, post and retention of Conceptual Change in Algebra Test were analyzed. Four classes of Tenth Graders from two schools (two classes for experimental group and the other two classes for control group) were choose randomly from 20 classes of 543 Grade Ten male students. Descriptive statistics such as mean and standard deviation was used to analysis Motivation to Engage in Conceptual Change Questionnaire (MECCQ).